Elevational patterns of hydrological properties of forest litter layers in Daming Mountain, southern China - Gang Hu; Chunlin Huo; Cong Hu; Chaofang Zhong; Siyu Chen; Chaohao Xu; Zhonghua Zhang (Global Ecology and Conservation, 2025)
Forest ecosystems is critical for the global water cycle and hydrological process in the world. As an indispensable composition of forest ecosystem, litter plays a vital role in rainfall interception and water retention. however, limited research has investigated the variation of litter physical properties and hydrological properties across mountainous altitudinal gradients. This study analyzed the changes in hydrological properties of forest litter and its response to environmental factors over eight altitudinal gradients (300–1400 m) in Daming Mountain, southern China. Results showed that elevation significantly influenced litter properties (litter thickness and mass) and hydrological properties (maximum water holding rate and capacity, and effective interception rate and capacity) of undecomposed and semi-decomposed litter layers. Both of litter mass and thickness initial increased and then decreased with increasing elevation, and the maximum and minimum value were at 700 and 1400 m, respectively. The maximum water holding rate and effective water interception rate in both semi-decomposed and undecomposed layers tended to increase from 500 to 1300 m, while others decreased. Laboratory soaking experiments also indicated that high elevation (≥ 700 m) and low elevation (≤ 500 m) affect the water absorption capacity of these two layers. In addition, partial least squares regression showed that the annual, maximum and minimum land surface temperature were the most important factors for maximum water holding rate and effective water interception capacity, while elevation was the moderate important factor for the litter hydrological properties and had significant high collinearity with other environmental factors. Therefore, the elevation might be an important factor in indirectly affecting litter hydrological properties though the directly influencing the temperature and vegetation factors.